Hominin dental remains from the Pliocene localities at Lomekwi, Kenya (1982–2009). Issue 145 (August 2020) - Skinner, Matthew M.; Leakey, Meave G.; Leakey, Louise N.; Manthi, Fredrick K.; Spoor, Fred
Abstract: Increasing evidence for both taxonomic diversity and early stone manufacture during the Pliocene highlights the importance of the hominin fossil record from this epoch in eastern Africa. Here, we describe dental remains from Lomekwi (West Turkana, Kenya), which date from between 3.2 and 3.5 Ma. The sample was collected between 1982 and 2009 and includes five gnathic specimens and a total of 67 teeth (mostly isolated permanent postcanine teeth). Standard linear dimensions indicate that, although the Lomekwi teeth are relatively small, there is broad overlap in size with contemporary Australopithecus afarensis and Australopithecus deyiremeda specimens at most tooth positions. However, some dental characters differentiate this sample from these species, including a relatively large P4 and M3 compared with the M1, a high incidence of well-developed protostylids, and specific accessory molar cuspules. Owing to a lack of well-preserved tooth crowns (and the complete absence of mandibular teeth) in the holotype and paratype of Kenyanthropus platyops, and limited comparable gnathic morphology in the new specimens, it cannot be determined whether these Lomekwi specimens should be attributed to this species. Attribution of these specimens is further complicated by a lack of certainty about position along the tooth row of many of the molar specimens. More comprehensive shape analyses of the external and internal morphology of these specimens, and additional fossil finds, would facilitate the taxonomic attribution of specimens in this taxonomically diverse period of human evolution.